FACILITIES FOR ANIMAL FEED PRODUCTION AS SALMONELLA RESERVOIRS AND SOURCES OF FINAL PRODUCTS CONTAMINATION - Bojana Prunić; Dubravka Milanov; Aleksandar Mašić; Sandra Jakšić; Ksenija Nešić (Archives of Veterinary Medicine, 2019)
Animal feed is the first link in the cycle “farm to fork” and the first potential place for entry of alimentary pathogens into the food chain. Special attention is given to bacteria from the genus Salmonella due to significant health and economic concerns related to salmonellosis in both human and veterinary medicine worldwide. Animal feed can become infected with salmonella through contaminated raw materials of animal and plant origin, but contamination of final products can occur during processing and postprocessing in facilities for their production. The life cycle of Salmonella species occurs partly in higher organisms, and partly in the living environment. Their ubiquitous distribution and survival in the environment (outside the host organism) in soil, water, on plant matter as well as on various artificial materials is made possible by the formation of multicellular communities known as the biofilm. Biofilms are multicellular bacterial formations that are irreversibly adhered to surfaces, incorporated into the extracellular substance produced by themselves and which exhibit significantly different properties (biofilm phenotype) in relation to those that grow in the suspension (planktonic phenotype). One of the most important characteristics of biofilm phenotype is the increased bacterial resistance to various stress factors in the environment, including chemical and thermal treatments, and the mechanical cleaning and sanitation. By creating the biofilm, salmonella enables its survival and persistence for months or years on equipment and working surfaces in animal feed production facilities. Due to the ubiquitous distribution of Salmonella species in nature, and therefore on plant matter as the primary raw material for the production of animal feed, it is unlikely that Salmonella could be eradicated from the food chain. Control measures should be directed to the prevention of contamination.